A hydroelasticity analysis of a damaged ship based on a two-way coupled CFD-DMB method. (15th April 2023) - Wei, Yujia; Incecik, Atilla; Tezdogan, Tahsin
Abstract: This study focuses on the numerical investigation of the hull girder loads on a flexible containership S175 with intact and damaged conditions advancing in regular head waves. In this study, a two-way coupled fluid-structure interactions framework is applied, in which the interactions between the flooding water inside the damaged tanks and wave fields are modelled by a Computational Fluid Dynamics toolbox OpenFOAM. The structural deformation is predicted using a multibody solver MBDyn. Hydroelasticity computations are performed for two different damage scenarios. The numerical results obtained show that the damaged ship experiences less vertical motions but greater global wave loads than the intact ship. It is also demonstrated that ship damages greatly influence the hull girder vertical bending moments (VBMs), while still water VBM is sensitive to the added weight from flooding water. In specific ship-damage conditions, local hogging moments at several amidship sections are found to exceed the limits specified by international regulations. Therefore, a new safety factor is recommended to avoid hogging moments of damaged ships remain below the limiting value. The results can also be used to determine whether the damaged ship will experience secondary damage due to hydroelastic response, helping with the design of future conventional ships. Highlights: A fully coupled 3D CFD-DMB model for ship hydroelasticity is introduced. The hull girder loads are predicted for an intact and damaged ship. The developed numerical method is validated systematically. A new safety factor is recommended for internarial regulation.